2012
DOI: 10.1088/1367-2630/14/3/033030
|View full text |Cite
|
Sign up to set email alerts
|

Optimal open-loop near-field control of plasmonic nanostructures

Abstract: Optimal open-loop control, i.e. the application of an analytically derived control rule, is demonstrated for nanooptical excitations using polarization-shaped laser pulses. Optimal spatial near-field localization in gold nanoprisms and excitation switching is realized by applying a π shift to the relative phase of the two polarization components. The achieved near-field switching confirms theoretical predictions, proves the applicability of predefined control rules in nanooptical light-matter interaction and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Optimal pulse shapes could be found using open-24 and closed-loop25 coherent control methods applied on the nanoscale. Improvements of sample preparation could also increase enhancement factors.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal pulse shapes could be found using open-24 and closed-loop25 coherent control methods applied on the nanoscale. Improvements of sample preparation could also increase enhancement factors.…”
Section: Discussionmentioning
confidence: 99%
“…We show that recently derived analytic control rules can also be employed experimentally and provide the desired nanooptical excitation in a direct fashion (Fig. 2d) [6]. …”
Section: Introductionmentioning
confidence: 77%
“…It is known that shaping the polarization and amplitude of incoming pulses of light can be used to switch between propagation paths or localized spots [3][4][5][6][7]. Recently, a series of works have shown that the interaction of monochromatic circularly polarized light with structures having one mirror-symmetry plane can result in asymmetric excitation of surface plasmons (surface electromagnetic waves in metals) toward mirror-symmetric directions, enabling the sorting of light into different directions according to its spin [8][9][10][11][12][13].…”
mentioning
confidence: 99%